Performance Medical Rehabilitation Installation Staff Dr Sardjito Hospital Yogyakarta - Wardo, Wardo; Sudarwati, Sudarwati; Istiatin, Istiatin (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence simultaneously (simultaneously) or partially of organizational culture variables, financial compensation, role conflict and social support on the performance of the Medical Rehabilitation Installation staff at Dr Sardjito Hospital Yogyakarta This research method uses a quantitative research design. The population of all employees working at the Medical Rehabilitation Installation at Dr Sardjito Hospital Yogyakarta is 55 people. The sampling technique used in this research was a purposive sampling technique with a sample size of 48 respondents. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that organizational culture, financial compensation, role conflict and social support influence the performance of the Medical Rehabilitation Installation staff at Dr Sardjito Hospital Yogyakarta. Suggestions from this research, the Medical Rehabilitation Installation of Dr Sardjito Hospital Yogyakarta continues to maintain and improve organizational culture, financial compensation, social support and minimize the atmosphere that creates role conflict for staff, so that employee performance will increase and be better than before. Key words: organizational culture, financial compensation, role conflict, social supportS